Enhancement of choleragen ADP-ribosyltransferase activities by guanyl nucleotides and a 19-kDa membrane protein. - Tsai, S C (1987)
Choleragen activates adenylate cyclase by catalyzing, in the presence of NAD, the ADP-ribosylation of Gs alpha, the stimulatory guanyl nucleotide-binding protein of the cyclase system. Kahn and Gilman [Kahn, R. A. & Gilman, A. G. (1986) J. Biol. Chem. 261, 7906-7911] identified another guanyl nucleotide-binding protein termed ADP-ribosylation factor (ARF) that stimulated this reaction. It was proposed that the toxin substrate is an ARF-Gs alpha complex and that ARF may have a physiological role in regulation of Gs alpha activity. We have found that purified ARF from bovine brain enhances not only the ADP-ribosylation of Gs alpha but also Gs alpha-independent choleragen-catalyzed reactions. These are (i) ADP-ribosylation of agmatine, a low molecular weight guanidino compound; (ii) ADP-ribosylation of several proteins unrelated to Gs alpha; and (iii) auto-ADP-ribosylation of the toxin A1 peptide. These reactions, as well as the ADP-ribosylation of ARF itself, were stimulated by GTP or stable GTP analogues such as guanyl-5'-yl imido-beta gamma-diphosphate and guanosine 5'-O-[gamma-thio]triphosphate; GDP and guanosine 5'-O-[beta-thio]diphosphate were inactive. These observations are consistent with the conclusion that ARF interacts directly with the A subunit of choleragen in a GTP-dependent fashion thereby enhancing catalytic activity manifest as transfer of ADP-ribose to Gs alpha and other proteins, to the toxin A1 peptide, or to agmatine. It is tempting to speculate that ARF may be involved in regulating one or another of the ADP-ribosyltransferases found in animal cells.